Highrise - common ground : art and the Amsterdam Zuidas area - Bavo; Boomgaard, Jeroen (Amsterdam : Valiz, 2008)
"The Amsterdam Zuidas area aims to become a new city center with offices, residential areas and cultural amenities. Its development is taking place within a 'state of exception'. However, the key issue remains the possible effect and significance for the position of culture and art in the public domain that emerges from this particularity. This book offers critical reflection on a variety of issues concerning the relationship between art and urban development and features theoretical contemplation as well as unique contributions by artists."--Page 4 of cover.
Published in English; some or all articles translated from Dutch?
boek